Effect of parental smoking on their children’s urine cotinine level in Korea: A population-based study - Park, Myung-Bae; Ranabhat, Chhabi Lal (PloS one, 2021)
Children may be exposed to tobacco products in multiple ways if their parents smoke. The risks of exposure to secondhand smoke (SHS) are well known. This study aimed to investigate the association between parental smoking and the children's cotinine level in relation to restricting home smoking, in Korea. Using the Korea National Health and Nutrition Health Examination Survey data from 2014 to 2017, we analyzed urine cotinine data of parents and their non-smoking children (n = 1,403), in whose homes parents prohibited smoking. We performed linear regression analysis by adjusting age, sex, house type, and household income to determine if parent smoking was related to the urine cotinine concentration of their children. In addition, analysis of covariance and Tukey's post-hoc tests were performed according to parent smoking pattern. Children's urine cotinine concentrations were positively associated with those of their parents. Children of smoking parents had a significantly higher urine cotinine concentration than that in the group where both parents are non-smokers (diff = 0.933, P < .0001); mothers-only smoker group (diff = 0.511, P = 0.042); and fathers-only smoker group (diff = 0.712, P < .0001). In the fathers-only smoker group, the urine cotinine concentration was significantly higher than that in the group where both parents were non-smoker (diff = 0.221, P < .0001), but not significantly different compared to the mothers-only smoker group (diff = - -0.201, P = 0.388). Children living in apartments were more likely to be exposed to smoking substances. This study showed a correlation between parents' and children's urine cotinine concentrations, supporting the occurrence of home smoking exposure due to the parents' smoking habit in Korea. Although avoiding indoor home smoking can decrease the children's exposure to tobacco, there is a need to identify other ways of smoking exposure and ensure appropriate monitoring and enforcement of banning smoking in the home.